Ning's igloo romance : a sequel to Ningiyuk's igloo world - Rokeby-Thomas, Anna E. (Chicago : Moody Press, 1975)
In the continuing adventures of Ning in her Arctic world, she finds romance and marries.
Keywords: Eskimos -- Fiction